Web engagement strategies in business, government and education sector: Review - Norita, Ahmad; Aziman, Abdullah (Penerbit UMP, 2021)
Web engagement is a user experience related to emotional, cognitive and behavioural interaction that connect to the goals and interests of the customers. There are seven (7) engagement metrics listed that used to measure web engagement. However, not all of these engagement metrics will help to achieve the objectives because each website have different purpose. There are various web engagement strategies used in business, government and education sectors that has their own way of engaging the web to ensure their success. In business sector, positive communication and experience with customers can make the customers stay long with the brand. In government, most of the services provided are to facilitate the people and to maintain the trust and support of the people. The E-Government 2.0 model was presented with an additional element of Web 2.0 technology. In education, Learning Managemeny System (LMS) and Massive Open Online Courses (MOOCs) are some of the approach in online learning. There are four (4) main features of online learning that are distance learning, connectivity and involvement, support and flexibility control to ensure the continuity of online learning.This reviewing will lead having in attention the aim of developing high-performance in online engagement.